How fixed mobile usage interact? Does FTTH deployment influence the interaction? - Julienne Liang (International Telecommunications Society (ITS), 2015)
We estimate the interaction between fixed and mobile usage both for voice and data services using consumer level data from April 2013 to March 2014 in a European country. We find a significant proportion of fixed voice consumption could be substituted by mobile voice, and vice versa. However, a substantial proportion of fixed data consumption, and also mobile data consumption, is generated by fixed-mobile interaction in both directions. FTTH deployment has no significant impact on fixed-mobile voice substitution. The fixed data consumption generated by mobile to fixed interaction appears to increase with FTTH deployment.
Keywords: L43; L50; L96; 330; Fixed mobile; fixed mobile usage interaction; voice consumption; data consumption; substitution versus complementarity; FTTH deployment